2011
DOI: 10.1111/j.1551-2916.2011.04959.x
|View full text |Cite
|
Sign up to set email alerts
|

CuInS2/N3 Co‐Sensitized ZnO Nanorods with Improved Photovoltaic Properties for Solar Cells

Abstract: Uniform core/shell nanostructure of ZnO/CuInS 2 nanorods was synthesized using ZnO nanorod arrays as reactive templates via solution reaction. The N3 dye was sequentially assembled on the ZnO/CuInS 2 arrays to construct a cascading co-sensitized nanomaterial as photoanode of solar cell. Formation process of CuInS 2 /ZnO nanostructure and the mechanism of CuInS 2 and N3 co-sensitization were discussed. The I-V characteristic measurement indicates an enhanced efficiency by 24.8% as compared to single sensitized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…It can be concluded that the CuInS 2 shell could enlarge the photoresponse spectrum to visible region, and the photoabsorption of the ZnO/CuInS 2 core/shell nanoarray was enhanced, which is related to the narrow energy band (bulk E g ¼ 1?53 eV) as well as the high optical absorption coefficient (10 5 cm 21 ) of CuInS 2 . 15,[18][19][20][21] With deposited CuSCN, the transmittance of as obtained heterostructure was not changed heavily, mainly due to the transparence of CuSCN in the visible light spectrum range. 11 Fig .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…It can be concluded that the CuInS 2 shell could enlarge the photoresponse spectrum to visible region, and the photoabsorption of the ZnO/CuInS 2 core/shell nanoarray was enhanced, which is related to the narrow energy band (bulk E g ¼ 1?53 eV) as well as the high optical absorption coefficient (10 5 cm 21 ) of CuInS 2 . 15,[18][19][20][21] With deposited CuSCN, the transmittance of as obtained heterostructure was not changed heavily, mainly due to the transparence of CuSCN in the visible light spectrum range. 11 Fig .…”
Section: Resultsmentioning
confidence: 88%
“…As we can see from curve a, the cathodic threshold potential for the reduction of Cu 2þ to Cu þ ions is about 2100 mV when using ZnO/CuInS 2 heterostructure as working electrode, and a shift of the g reduction potential to a more negative range as well as a decrease in the cathode reaction current density could be observed. Owing to the stepwise band gap between ZnO and CuInS 2 , described as in our previous work, 15 the transport of electrons from ZnO to CuInS 2 would be blocked to some degree, and it would make it harder for Cu 2þ to gain electrons from the surface of ZnO/CuInS 2 heterostructure, which is the key step (Cu 2þ þ e 2 RCu þ , Cu þ þ SCN 2 RCuSCNQ) for the deposition of CuSCN into the heterostructured nanorods array. Thus, the electrodeposition speed of CuSCN would be decreased, corresponding to the variation tendency of the curves shown as Fig.…”
Section: Resultsmentioning
confidence: 99%
“…But still this approach has to be improved due to the hydrophilic nature of TiO 2 nanotubes. Co-sensitization by hybrid on ZnO photoanode was found to be improving efficiency through CuInS 2 /N3 combination [144]. Interestingly, hierarchical structure of ZnO/ZnS Review SN Applied Sciences (2019) 1:186 | https://doi.org/10.1007/s42452-018-0054-3…”
Section: Co-sensitization By Hybrid (Dye/quantumdots) On Tio 2 Photoementioning
confidence: 99%
“…In the past, photoanodes were improvised using nano-architectures, [3][4][5] light scattering layer, 6,7 composite with another semiconductor [8][9][10] or graphene, 11,12 doping, [13][14][15] interfacial engineering 16,17 and TiCl 4 post-treatment methods. 18,19 For instance, various nanoforms of ZnO was used as cascading co-sensitized nanomaterial which enhanced the efficiency of dye sensitized solar cells 20,21 and Vanadium doped TiO 2 is used to fabricate the working electrode in a DSSCs by layer-by-layer method was explored a remarkable performance compared to bare TiO 2 particles 22 .…”
Section: Introductionmentioning
confidence: 99%